Brannigans Land: Mean and Evil - Book 2 - Johnstone, William W.; Johnstone, J. A. (Thorndike, Maine : Center Point Large Print, 2022)
"As a man who traded his tin star for a cattle ranch and a family, Ty Brannigan loves his wife and children. And may Lord have mercy on those who would harm them -- because Ty Brannigan will show none. No one knows their way around a faro table, bank vault, or six shooter more than Smilin Doc Ford. When hes not gambling or thieving, hes throwing lead -- or, if hes feeling especially vicious, slitting throats with his Arkansas toothpick. Roaming the west with Doc is a band of wild outlaws including a pair of hate-filled ex-cons and the voluptuous Zenobia "Zee" Swallow, Docs kill-crazy lady. The gang have been on a killing spree, leaving a trail of bodies near Ty Brannigans Powderhorn spread in Wyomings Bear Paw Mountains. U.S. marshals want Ty to help them track down Smilin Docs bunch. But when the hunt puts the Brannigan clan in the outlaws sights, Ty and his kin take justice into their own hands -- and deliver it with a furious, final vengeance."--
Keywords: Ranchers -- Fiction; Families -- Fiction; Outlaws -- Fiction; Wyoming -- Fiction; Western fiction